A semi-analytical non-iterative primary approach based on priority list to solve unit commitment problem. (August 2015) - Moradi, Saeed; Khanmohammadi, Sohrab; Hagh, Mehrdad Tarafdar; Mohammadi-ivatloo, Behnam
Abstract: For many years, the UC (unit commitment) problem has been solved by complex numerical techniques or intelligent search algorithms, due to nonlinear and complex constraints. Many of the applied algorithms employ random searches, which leads to production of different solutions in different program runs. Priority list-based methods are a way out to this, as they produce robust results during a non-iterative procedure, and without help of trial and error efforts. Nevertheless, they have all proven inefficient. This paper introduces a new approach that generates the solutions using algorithm-specific constraint handling techniques, based on the priority list concept. The solution-making stages include: 1. Minimum up/down time establishment using a probabilistic priority list-oriented selection mechanism, 2. Spinning reserve constraint handling through a deterministic priority list-based process, 3. Power balance handling and a ramp rate modification procedure for generating efficient ramp-constrained solutions. The different steps are designed such that efficient modifications are applied in each step without violating the previously established constraints. Simulation results on different test systems reveal that the approach obtains robust and competitive results. A new 140-unit large-scale test system based on Korean power system is also presented for verifying applicability of the proposed approach on real world power systems. Highlights: Priority list is employed to develop a new approach for thermal UC problem. New constraint handling techniques are designed for different UC constraints. Results are reported for 10-to-100-unit and IEEE 24 and 118-bus test systems. The approach yields robust results i.e. identical solutions in different runs. The large-scale 140-unit modified Korean power test system has been introduced.